2021
DOI: 10.1002/ece3.7364
|View full text |Cite
|
Sign up to set email alerts
|

Seven decades of southern range dynamics of Canada lynx

Abstract: Over the past century, the range of many species has changed, often attributed to climate change and land cover modification (Laliberte & Ripple, 2004;Thomas, 2010;Walther et al. 2002). A species can respond to environmental changes by exploiting resources at the extremities of its niche (Sexton et al. 2017), by phenotypic plasticity (Nicotra et al. 2010;Valladares et al. 2014) or by adaptation (Williams et al. 2008). However, the rate at which current conditions are changing might make adaptation impossible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Ecological specialization is also widely predicted to arise in environments with greater species richness owing to more opportunity for community-level interactions (Kartzinel et al, 2015;Granot and Belmaker, 2019). Mechanisms underlying patterns in niche breadth and overlap we observed could be important for understanding range expansion and retraction of bobcat and Canada lynx, respectively (Koen et al, 2014;Marrotte and Bowman, 2021). A recent study suggested that trophic niches based on resource use (i.e., Eltonian niche) may be more relevant to the distribution of species at fine spatial scales, while habitat niches based on climate or environmental conditions (i.e., Grinnellian niche) may be more important across large geographic scales (Stevens, 2022).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Ecological specialization is also widely predicted to arise in environments with greater species richness owing to more opportunity for community-level interactions (Kartzinel et al, 2015;Granot and Belmaker, 2019). Mechanisms underlying patterns in niche breadth and overlap we observed could be important for understanding range expansion and retraction of bobcat and Canada lynx, respectively (Koen et al, 2014;Marrotte and Bowman, 2021). A recent study suggested that trophic niches based on resource use (i.e., Eltonian niche) may be more relevant to the distribution of species at fine spatial scales, while habitat niches based on climate or environmental conditions (i.e., Grinnellian niche) may be more important across large geographic scales (Stevens, 2022).…”
Section: Discussionmentioning
confidence: 76%
“…The two species thus occur in sympatry only across the Canada-United States border and in the Rocky Mountains (Peers et al, 2013). Increased abundance of bobcats as well as their recent range expansion (Lavoie et al, 2009;Roberts and Crimmins, 2010), and reductions in lynx abundance and range retraction (Koen et al, 2014b;Marrotte and Bowman, 2021) could also be related to dietary niche variation for one or both species. We evaluated dietary niche position, breadth and overlap for Canada lynx and bobcat using stable isotope analysis of hair and fur samples collected from multiple regions spanning their sympatric range.…”
Section: Introductionmentioning
confidence: 99%